Historical archaeology in Magna Graecia: From an American perspective to the Greek colonization in South Italy (Heródoto: Revista do Grupo de Estudos e Pesquisas sobre a Antiguidade Clássica e suas Conexões Afro-asiáticas, 2018)
The historical archaeology approach was forged for the study of the American society after the European conquest of colonial lands in the new continent. Interested in the comparison between material culture and written records, it was opposed to Prehistory and Anthropology with their methods of inquiry. Its main proposal is to use all available data, material and written, independently, without any hierarchy, but in close comparison. As such, this perspective studies the archaeology of individuals “without history”, such as Natives, slaves, women, or even the African diasporas in America, in antagonism to the white male European colonist. Issued from an explicit postcolonial background, this approach may give an important contribution to the study of other ancient societies where interpretations are based on discussions between archaeological remains and texts, such as the Greek colonial communities in Magna Graecia.